Biomass-Derived Activated Carbon via Na₂CO₃, KOH, and ZnCl₂ Activation: A Comparative Physicochemical Study toward Energy Storage Electrodes - Bakti, Andi Ikhtiar; Rio, Afrioni Roma; Mosey, Handy Indra Regain; Jumriadi, Jumriadi (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2025)
This study investigates the fabrication of granular activated carbon (AC) from biomass waste using three chemical activating agents: sodium carbonate (Na₂CO₃), potassium hydroxide (KOH), and zinc chloride (ZnCl₂), to evaluate their effects on structural, morphological, and electrical properties relevant to energy storage applications. An experimental laboratory-based method with a comparative activation approach was employed. The resulting activated carbon samples were characterized by X-ray diffraction (XRD), scanning electron microscopy coupled with energy-dispersive spectroscopy (SEM–EDS), and iodine adsorption and electrical measurements. XRD analysis revealed that all samples predominantly exhibit amorphous or turbostratic carbon structures with partial structural ordering, with ZnCl₂-activated samples showing higher short-range ordering than those activated with the other activators. SEM observations indicated qualitative differences in surface morphology and pore development, with more pronounced pores in the KOH-activated carbon. EDS analysis confirmed carbon-rich surfaces with minor residual inorganic elements originating from the activating agents and biomass precursor. Iodine adsorption results, used as a proxy indicator of microporosity, showed that the KOH-activated carbon exhibited the highest iodine number (630.70 mg/g). Electrical measurements, reported as apparent electrical conductivity under the applied packed-bed measurement conditions, also indicated the highest value for the KOH-activated sample (1724.10 S/m). Based on the parameters measured in this study, KOH activation produced the most favorable combined iodine adsorption and apparent electrical conductivity among the activation routes investigated. Therefore, KOH-activated biomass-derived carbon is identified as the most promising candidate for subsequent electrochemical validation toward supercapacitor electrode applications.